2001
DOI: 10.1046/j.1464-4096.2001.001223.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum chromogranin‐A in advanced prostate cancer

Abstract: Objective To determine the value of serum chromogranin A (CgA), a marker of neuroendocrine differentiation, for monitoring prostate cancer; CgA levels were related to three other tumour markers, i.e. total prostate‐specific antigen (tPSA), prostatic acid phosphatase (PAP), neurone‐specific enolase (NSE), and to testosterone, to assess the importance of hormone withdrawal. Patients and methods Serum samples (218) were obtained from 118 patients with prostate cancer, including 111 patients with advanced prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 31 publications
1
40
0
4
Order By: Relevance
“…9,16 CgA may predict response to chemotherapy, 17,18 and as a marker of NE differentiation CgA has been shown to reflect androgen-independent disease even before evidence of PSA progression. 19,20 Some have suggested that CgA velocity may be useful in predicting time to androgen independence after hormonal therapy and have indicated that treatments variably accelerate NE differentiation (intermittent androgen deprivation oantiandrogen only ocastration only ocombined androgen blockade). 16,19 In the androgen-independent CaP patient, increased CgA levels appear to correlate with adverse outcomes and decreased overall survival, though levels indicative of a survival disadvantage are undefined (Table 2).…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…9,16 CgA may predict response to chemotherapy, 17,18 and as a marker of NE differentiation CgA has been shown to reflect androgen-independent disease even before evidence of PSA progression. 19,20 Some have suggested that CgA velocity may be useful in predicting time to androgen independence after hormonal therapy and have indicated that treatments variably accelerate NE differentiation (intermittent androgen deprivation oantiandrogen only ocastration only ocombined androgen blockade). 16,19 In the androgen-independent CaP patient, increased CgA levels appear to correlate with adverse outcomes and decreased overall survival, though levels indicative of a survival disadvantage are undefined (Table 2).…”
Section: Markers Of Neuroendocrine Differentiationmentioning
confidence: 99%
“…As such, it may be possible to use chromogranin A to monitor metastatic PCa patients under androgen blockade. 90,91 Novel blood biomarkers for prostate cancer K Bensalah et al…”
Section: Chromogranin Amentioning
confidence: 99%
“…[39] Tumors with NE features have displayed more aggression and are more resistant to hormone therapy. [25] Some studies have claimed that CgA is an independent prognostic marker for PCa, [40] while others have conflicted with these findings. [29,41] No PCa predictive values were seen for IGF-1, IGFBP-3 or CgA; AUC were 0.58, 0.55 and 0.56, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to use CgA to monitor metastatic PCa patients under androgen blockade. [25] Some indicate CgA utility in early diagnosis, particularly when used in combination with free/total PSA ratio, [26] however, some studies found that CgA does not precisely differentiate malignant disease. [27] Similar debate occurs regarding CgA and tumor features [28] and CgA does not show any advantage in the prognosis of PCa recurrence after radical prostatectomy or radiotherapy.…”
Section: Introductionmentioning
confidence: 99%